94.2k views
0 votes
HELP ME PLEASE WITH THIS QUESTION! :D

HELP ME PLEASE WITH THIS QUESTION! :D-example-1
User Kanishk
by
5.5k points

1 Answer

6 votes

Answer:

see explanation

Explanation:

Using the rule of exponents


a^(m) ×
a^(n) =
a^((m+n))

(a)

3 × a × 2 × b

= 3 × 2 × a × b

= 6ab

(b)


c^(5) × c

=
c^((5+1))

=
c^(6)

(c)

2
y^(4) × 5y³

= 2 × 5 ×
y^(4) × y³

= 10 ×
y^((4+3))

=10
y^(7)

(d)

3gh² × 4g³h³

= 3 × 4 × g × g³ × h² × h³

= 12 ×
g^((1+3)) ×
h^((2+3))

= 12
g^(4)
h^(5)

User KiwiJuicer
by
6.6k points